The evaluation of a training program for teachers inadult education in Peru - Perales Montolío, María Jesús (2018)
We present the evaluation of a training program with teachers of adult education. The Seminario en Gestión Pedagógica para Directores, Subdirectores y Docentes nombrados de los Centros de Educación Básica Alternativa Públicosis conducted in Spain from the University ofValencia. The program is designed based on a consensus process between the institutions and authorities involved, linking an adequate analysis of previous needs. Likewise, the seminar is designed combining three training approaches: lectures on specific topics, visits to places and different educational resources and training courses. Designinga training program on adult education for a specific group, from its implementation, should be analyzed and evaluated to highlight elements and aspects to improve, as well as analyzing the characteristics that have worked properly or have appearedas unexpectedlyin the developmentprocess. To do this, this study worked with the 99 teachers of EBA active, participants in the seminar, so they could perform an analysis from different approaches to approximate results and data. A mixed methodology wasdeveloped with statistical analysis on quantitative data and content analysis on qualitative results, based on a survey study, murals and photography exhibition. The results, in general, are adequate in both waysin all the cases studied. The evaluation of the product has been very enriching to be able to make decisions after its realization and to continue advancing in the improvement of this type of teacher training programs.